Flagellar elongation and shortening in Chlamydomonas. IV. Effects of flagellar detachment, regeneration, and resorption on the induction of flagellar protein synthesis (The Rockefeller University Press, 1978)
Synthesis of new proteins is required to regenerate full length Chlamydomonas flagella after deflagellation. Using gametes, which have a low basal level of protein synthesis, it has been possible to label and detect the synthesis of many flagellar proteins in whole cells. The deflagellation-induced synthesis of the tubulins, dyneins, the flagellar membrane protein, and at least 20 other proteins which co- migrate with proteins in isolated axonemes, can be detected in gamete cytoplasm, and the times of initiation and termination of synthesis for each of the proteins can be studied. The nature of the signal that stimulates the cell to initiate flagellar protein synthesis is unknown. Flagellar regeneration and accompanying pool depletion are not necessary for either the onset or termination of flagellar protein synthesis, because colchicine, which blocks flagellar regeneration, does not change the pattern of proteins synthesized in the cytoplasm after deflagellation or the timing of their synthesis. Moreover, flagellar protein synthesis is stimulated after cells are chemically induced to resorb their flagella, indicating that the act of deflagellation itself is not necessary to stimulate synthesis. Methods were defined for inducing the cells to resorb their flagella by removing Ca++ from the medium and raising the concentration of K+ or Na+. The resorption was reversible and the flagellar components that were resorbed could be re-utilized to assemble flagella in the absence of protein synthesis. This new technique is used in this report to study the control of synthesis and assembly of flagella.